PENERAPAN ASKEP DENGAN GANGGUAN SISTEM REPRODUKSI CA SERVIKS DALAM PEMENUHAN KEBUTUHAN RASA NYAMAN (NYERI) Application Of Nursing Care With Servical Cancer in Fulfilling Comfortable Needs (Pain) - Zulfia Samiun (Media Keperawatan:Politeknik Kesehatan Makassar, 2019)
AbstractBackground: Cervical cancer is a leading cause of death among women worldwide. It is estimated that 274,000 deaths occur each year due to this preventable disease. According to the World Health Organization (2013) quoted from Rachmawati (2014), deaths from breast cancer and cervical cancer in 2011 were 273,500. Deaths and in 2010 totaled 247,000, in Indonesia every year the number of patients with cervical cancer according to the Indonesian Cervical Cancer Care Foundation (2012), in Indonesia each year the number of patients with cervical cancer is very high, 15,000 cases. This was stated to be equivalent to 40 women suffering from cervical cancer and 20 of them died. In 2030, in Indonesia the number of patients with cervical cancer is expected to experience a 7-fold increase.Purpose: to carry out nursing care for Ny "D" clients with reproductive system disorders Ca. Cervix in the room of Baji Gau I RSUD Labuang Baji Makassar.Method: The design used in this study is a case study which is to provide nursing care to the client "D" with a reproductive system disorder Ca. Cervix in the Baji Gau I room at Labuang Baji Hospital Makassar.Results: From the results of the study it was found that nursing diagnoses of pain were associated with infiltration of cancer cells to tissues. Interventions are based on existing theories. Implementation is carried out based on the intervention that has been made. After the implementation is carried out, the evaluation / results of the problem have not been resolved.Conclusion: Pain nursing diagnoses associated with infiltration of cancer cells to tissues after implementation for 3 days obtained results of nursing problems have not been resolved. Keywords: Askep, Cervical Ca, Pain        AbstrakLatar Belakang : Kanker serviks merupakan penyebab utama kematian di antara perempuan di seluruh dunia. Diperkirakan bahwa 274.000 kamatian terjadi setiap tahun akibat penyakit yang dapat dicegah ini. Menurut World Health Organization (2013) dikutip dari Rachmawati (2014), kematian akibat kanker payudara dan kanker seviks pada tahun 2011 sebanyak 273.500. Kematian dan pada tahun 2010 sebanyak 247.000, di Indonesia setiap tahun jumlah penderita kanker serviks Menurut Yayasan Peduli Kanker Serviks Indonesia (2012), di Indonesia setiap tahunnya jumlah penderita kanker serviks sangat tinggi yaitu 15.000 kasus. Hal ini dinyatakan setara dengan 40  wanita menderita kanker serviks dan 20 diantaranya meninggal. Pada tahun 2030, di Indonesia jumlah penderita kanker seviks diperkirakan akan mengalami peningkatan 7 kali lipat.Tujuan : untuk melaksanakan asuhan keperawatan pada klien Ny “D” dengan gangguan sistem reproduksi Ca. Serviks diruang Baji Gau I RSUD Labuang Baji Makassar. Metode : Desain yang digunakan dalam penelitian ini adalah study kasus yakni memberikan asuhan keperawatan pada klien Ny “D” dengan gangguan sistem reproduksi Ca. Serviks di ruang Baji Gau I RSUD Labuang Baji Makassar. Hasil : dari hasil pengkajian ditemukan diagnosa keperawatan nyeri berhubungan dengan infiltrasi sel kanker ke jaringan. Intervensi ditegakkan berdasarkan teori yang ada. Implementasi dilakukan berdasakan intervensi yang telah dibuat. Setelah dilakukan implementasi didapatkan evaluasi/hasil masalah belum teratasi.Kesimpulan : diagnosa keperawatan nyeri berhubungan dengan infiltrasi sel kanker ke jaringan setelah dilakukan implementasi selama 3 hari diapatkan hasil masalah keperawatan belum teratasi.  Kata kunci : Askep, Ca Serviks, NyeriPENERAPAN ASKEP DENGAN GANGGUAN SISTEM REPRODUKSI CA SERVIKS DALAM PEMENUHAN KEBUTUHAN RASA NYAMAN (NYERI)  Application Of Nursing Care With Servical Cancer in Fulfilling Comfortable Needs (Pain)